Autobiografi Dato' Dusuki Ahmad : dari pondok ke parlimen - Dusuki Haji Ahmad (Yayasan Darul Hanan, 2010)
Autobiography of Dusuki Ahmad, a politician, Muslim scholar, and political secretary to the prime minister of Malaysia from 2000 to 2003